2022
DOI: 10.1128/mbio.02064-22
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Targets STING-Driven Antiviral Responses

Abstract: Several reports suggest that Genistein exhibits antiviral activities against DNA viruses. Our work uncovers a previously unrecognized proviral effect of Genistein, through inhibition of the cGAS-STING pathway at the level of cGAMP transfer and its sensing by STING. This suggests that the use of Genistein as an antiviral should be taken with caution as it may reduce the protective antiviral effects elicited by host STING activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Michael Gantier (Hudson Institute of Medical Research, Australia) closed the session with a presentation about pharmacological inhibition of TBK1/IKKε that blunts COVID-19 immunopathology. TANK-binding kinase 1 (TBK1) is a key signaling component that drives the production of type-I interferons (IFNs), which have essential antiviral activities including against SARS-CoV-2 . TBK1 and its homologue IκB kinase-ε (IKKε) can also induce the production of proinflammatory factors that contribute to pathogen clearance.…”
Section: Daymentioning
confidence: 99%
See 1 more Smart Citation
“…Michael Gantier (Hudson Institute of Medical Research, Australia) closed the session with a presentation about pharmacological inhibition of TBK1/IKKε that blunts COVID-19 immunopathology. TANK-binding kinase 1 (TBK1) is a key signaling component that drives the production of type-I interferons (IFNs), which have essential antiviral activities including against SARS-CoV-2 . TBK1 and its homologue IκB kinase-ε (IKKε) can also induce the production of proinflammatory factors that contribute to pathogen clearance.…”
Section: Daymentioning
confidence: 99%
“…TANK-binding kinase 1 (TBK1) is a key signaling component that drives the production of type-I interferons (IFNs), which have essential antiviral activities including against SARS-CoV-2. 64 TBK1 and its homologue IκB kinase-ε (IKKε) can also induce the production of proinflammatory factors that contribute to pathogen clearance. Initially, Gantier demonstrated that the anticancer small molecule idronoxil (IDX) directly inhibits human and mouse stimulators of interferon (IFN) genes (STING) signaling by destabilizing TBK1/IKKε/STING signaling complexes.…”
Section: ■ Daymentioning
confidence: 99%
“…Genistein ( GEN ) is the most effective active ingredient in isoflavones. It has the “dual biological effects” of estrogen-like and antiestrogen and plays a variety of potential functions, such as regulating lipid metabolism, antioxidation, and immune function ( Gao et al, 2021 ; Ullah et al, 2022 ; Ding et al, 2023 ). As an estrogen analog, GEN has been shown to play a variety of beneficial roles mainly by activating estrogen receptors ( ERs ), including G protein-coupled estrogen receptor ( GPR30 ), ERβ, and ERα ( Xiao et al, 2019 ; Vásquez-Reyes et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%